An Unusual Cause of Acute Kidney Injury in Pregnancy: Beware of HELLP Look-Alikes - Oralia Alejandra Orozco-Guillen; Virgilia Soto-Abram; Bernardo Moguel-Gonzalez; Magdalena Madero; Giorgina Barbara Piccoli (MDPI AG, 2022)
The differential diagnosis between new occurrence or revelation of chronic kidney diseases in pregnancy and hypertensive disorders of pregnancy is not easy, and the presence of a hypertensive disorder superimposed on a glomerular disease is even more challenging, as this case exemplifies. A 29-year-old woman was referred with HELLP (hemolysis, elevated liver enzymes, low platelets) syndrome at the end of her pregnancy. Immediately after cesarean delivery, she developed anuria, unexplained by blood loss or hypotension, and in the absence of known nephrotoxic drugs. While the laboratory features of HELLP rapidly resolved, AKI persisted, and the finding of high-level proteinuria was the hint leading to diagnosis of a glomerular disease (focal segmental glomerulosclerosis, FSGS), later proven by kidney biopsy. This case, reporting on the rare association between HELLP and FSGS, offers the opportunity to discuss the role of proteinuria, hypertension, and in the differential diagnosis of pregnancy-related acute kidney injury (pAKI).